Peran Penting Keluarga dalam Menjaga dan Merawat Individu yang Mengalami Gangguan Jiwa - Deni Suwardiman (Faletehan Health Journal, 2023)
The mental health issue experienced by individuals with mental disorders (MD) is a serious concern that necessitates a significant amount of time for recovery. Hence, family support as a pillar in the healing process becomes exceptionally crucial. Stigma associated with mental disorders exists. Consequently, a study is imperative to uncover the role of families in developing the intervention programs for individuals with MD, serving as a foundational step in designing contextually appropriate strategic approaches. The aim of this study was to ascertain the optimal family support requirements for caring for individuals experiencing mental disorders in Banten Province. The research employed a quantitative descriptive approach with the sample size of 103 respondents. The research findings indicated that the majority of families (53.4%) provided effective support for individuals with MD. Within the realm of the provided sub-support, a significant portion of families offered emotional support (51.5%), instrumental support (52.4%), evaluative support (52.4%), and informational support (55.3%). These findings showed that the program was unoptimal. Innovations and efforts to improve family role and community participation are needed in mental health intervention programs through the four aspects of family support.